Transcriptome Analyses Reveal Key Roles of Alternative Splicing Regulation in Atlantic Salmon During the Infectious Process of Piscirickettsiosis Disease - Vidal-Soto, R (Elsevier Ltd, 2023)
In the Chilean salmon farming industry, infection by Piscirickettsia salmonis is the primary cause of the main bacterial disease known as Piscirickettsiosis, which has an overwhelming economic impact. Although it has been demonstrated that Piscirickettsiosis modifies the expression of numerous salmonids genes, it is yet unknown how alternative splicing (AS) contributes to salmonids bacterial infection. AS, has the potential to create heterogeneity at the protein and RNA levels and has been associated as a relevant molecular mechanism in the immune response of eukaryotes to several diseases. In this study, we used RNA data to survey P. salmonis-induced modifications in the AS of Atlantic salmon and found that P. salmonis infection promoted a substantial number (158,668) of AS events. Differentially spliced genes (DSG) sensitive to Piscirickettsiosis were predominantly enriched in genes involved in RNA processing, splicing and spliceosome processes (e.g., hnRNPm, hnRPc, SRSF7, SRSF45), whereas among the DSG of resistant and susceptible to Piscirickettsiosis, several metabolic and immune processes were found, most notably associated to the regulation of GTPase, lysosome and telomere organization-maintenance. Furthermore, we found that DSG were mostly not differentially expressed (5–7 %) and were implicated in distinct biological pathways. Therefore, our results underpin AS achieving a significant regulatory performance in the response of salmonids to Piscirickettsiosis. © 2023 The Authors